GAMBARAN VOLUME SALIVA PADA LANSIA - nuni anggraeni; Neneng Nurjanah; Denden Ridwan Chaerudin; Tri Widyastuti (Politeknik Kesehatan Kemenkes Bandung, 2020)
Saliva is instrumental in the health of the oral cavity. Saliva serves for tissue lubrication in the oral cavity, protects the tissues in the oral cavity so as to avoid abrasion as the zhevanijam progresses, and Saliva also helps maintain the stability of the buffer system in the oral cavity. Elderly tend to have less saliva volumes due to the degenracy of organs in the saliva gland. In saliva secretions less than 0.06 ml/min (3 ml/h) will arise dry mouth complaints. The study aims to figure out the description of the saliva volume in the elderly. The method used in this research is the study of literary studies, which is research conducted through the collection of data that is library. The data taken for this research is secondary data from some research. The results of this study showed that the higher the age of saliva volume will continue to decline. Key words: elderly, saliva